EFFECTIVENESS OF THE MOM UUNG BREASTMILK BOOSTER SUPPLEMENT IN ENHANCING BREASTMILK PRODUCTION AMONG WORKING AND NON-WORKING MOTHERS - Mahmudiono, Trias; Rachmah, Qonita; Pratiwi, Azizah Ajeng; Rahmani, Alinda; Yusryana, Eka Anisah; Andamarai, Natasya Ayu; Agustin, Asri Meidyah (Universitas Airlangga, 2025)
Breastfeeding provides optimal nutrition for infants and offers significant health benefits to both mother and child. However, challenges such as perceived low milk production and workplace constraints hinder breastfeeding practices among mothers. This study evaluates the effectiveness of the Mom Uung Breastmilk Booster Supplement (BBS) in enhancing breastmilk production among working and non-working mothers. Using a cross-sectional design, data were collected from 665 breastfeeding mothers in Indonesia via a validated online questionnaire. Mothers who consumed X BBS reported increased breastmilk volume, breastfeeding frequency, and pumping efficiency, with significant improvements observed in both working and non-working groups (p<0.001). Non-working mothers demonstrated higher breastmilk production compared to working mothers. Key barriers identified included perceived low milk supply (30.3%) and work-related time constraints (11.6%). The study highlights the potential of X BBS to support breastfeeding practices and underscores the need for workplace policies that promote breastfeeding. Further research is recommended to validate these findings and objectively assess the impact of BBS on breast milk quantity and quality.